Normal superior vena cava flow and its correlation with left ventricular output in late preterm and term neonates at day one of life - Soni, Jai Prakash; Verma, Suresh Kumar; Goyal, Vishnu Kumar; Dhakar, Mukesh Kumar; Choudhary, Sandeep (Asian Journal of Medical Sciences, 2021)
Background: Assessment of systemic blood flow helps in choosing the appropriate drug for managing critically ill neonates with poor perfusion. Superior vena cava (SVC) flow has the potential to become a bedside gold standard method for this purpose. Aims and Objectives: To find out normal superior vena cava (SVC) flow and its correlation with left ventricular output (LVOT) in late preterm and term neonates. Materials and Methods: A cross sectional observational study was carried out at a tertiary care teaching hospital where SVC flow and left ventricular output were measured in hundred intramural healthy neonates (50 late pre-term, weighing 1500g or more and 50 term, weighing 2500g or more). SVC flow was correlated with LV output in both groups. Pearson correlation coefficient was calculated to correlate between two variables. p < 0.05 was considered significant. Results: Median SVC flow in late pre-term group was 57.83ml/kg/min, and in term neonates was 56ml/kg/min. In late pre-term babies correlation of SVC flow with LV output was better in comparison to term group (r-0.56, p<0.0001, and r-0.40, p=0.0024respectively). Conclusions: SVC flow better represents systemic blood flow in late preterm neonates in comparison to term neonates.